Implementasi Model PBL dengan Liveworksheet untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa SMPN 9 Medan: Penelitian - Erwin Syahputra; Imelda Sihombing (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study was conducted to improve the problem-solving skills of class VIII-2 students of SMPN 9 Medan in mathematics learning with the topic of Investigating the Properties of Geometric Figures. Learning was carried out using Live Worksheet as a learning media with the Problem Based Learning (PBL) as method. The object of this study was to improve problem-solving skills in learning to Investigate the Properties of Geometric Figures in class VIII-2 students of SMPN 9 Medan in the 20024/2025 academic year. This study used the Classroom Action Research (CAR) method which focused on Cycle I and Cycle II. In this study, the instruments used were teacher observation and tests (pre-test, post-test I and post-test II). Based on the data that has been analyzed, it was obtained that students' problem-solving skills increased from cycle I to cycle II with an N-Gain index of 0.56 with the category "Medium". Therefore, the researcher concluded that the application of Problem Based Learning using Live Worksheet can improve problem-solving ability in learning to Investigate the Properties of Geometric Figures in class VIII-2 students of SMPN 9 Medan.